The Influence of Facility and Service Quality towards Customer Satisfaction and Its Impact on Customer Loyalty in Borobudur Hotel in Jakarta - Rianto Nurcahyo; Annisa Fitriyani; Irma Nur Hudda (Bina Nusantara University, 2017)
Hotel developments currently grow very rapidly. The emergence of new hotels increases the competition in the hospitality industry. This research aimed to determine the influence of the facilities, the quality of service to customer satisfaction and its impact on customer loyalty in Borobudur Hotel in Jakarta. Data collection were done by distributing questionnaires directly to 360 customers in Borobudur Hotel, Jakarta. The analysis technique used path analysis. The results of this research indicate that the variables of facilities, service quality, and customer satisfaction significantly affect customer loyalty variables simultaneously or partially. In addition, facilities and quality of service variable have a significant effect on customer satisfaction variables.